Gender Based Differences in Promotions of Clerical Workers - Swimmer, Gene (Relations industrielles / Industrial Relations, 1990)
This paper aims at empirically addressing the issue of whether promotions of female clerical employees are less likely, when educational and other qualifications are held constant.